Implementasi Media Pembelajaran IPA Berbasis Adobe Flash CS6 untuk Meningkatkan Kemampuan Metakognisi Siswa SMP - Budhiman, Arief; Subali, Bambang; Supriyadi, Supriyadi (UPEJ Unnes Physics Education Journal, 2021)
Media is one thing which support learning proccess. This study aims to apply learning media based Adobe Flash CS6 to improve students’ metacognition ability. The research examined the implementation of learning media IPA based Adobe Flash CS6 in improving junior high schhool students’ metacognition ability. The method used was an experiment, with Quasi-Experimental Design using pretest and postest one grup design technique. The sampling used was purposive sampling. The result showed that the average score of pretest was (42.03) and the average score of postest was (72.03). Improved metacognition ability was shown by the N-gain test (0.52) with ‘medium criterion’. Students’ response test after learning media IPA based Adobe Flash CS6 to improve students’ metacognition ability obtained a percentage of (82,87) with ‘high criterion’. In conclution, learning media IPA based Adobe Flash CS6 can used to improve students’ metacognition ability.